Effects of glucocorticoid agonist and antagonist on the pathogenesis of L-arginine-induced acute pancreatitis in rat - Paszt Attila (PANCREAS, 2008)
Objectives: To investigate the consequences of treatment with an exogenous glucocorticoid agonist (methylprednisolone) and antagonist (RU-38486) on the local and systemic responses in L-arginine-induced acute pancreatitis in rats. Methods: The methylprednisolone and RU-38486 were administered just before pancreatitis induction. Plasma amylase activity, interleukin 6 activity, pancreatic weight/body weight ratio, plasma macrophage migration inhibitory factor (MIF) concentration, and pancreatic nuclear transcription factor (NF) kappa B activity were determined. The extents of pancreas, liver, and lung injurieswere assessed by histology. Results: Acute pancreatitis resulted in NF-kappa B activation and proinflammatory cytokine release in rats. In the glucocorticoid agonist group, plasma amylase and interleukin 6 levels were significantly decreased as compared with those of RU-38486 and nontreated groups. Antagonist treatment led to significantly higher MIF production at 8 and 12 hours after L-arginine injection as compared with the agonist-treated and nontreated groups. Glucocorticoid agonist treatment significantly decreased the level of NF-kappa B 24 hours after pancreatitis induction. Histological investigations showed protective effect of agonist treatment on acute pancreatitis-induced tissue damage in the pancreas and lung. Conclusions: These results corroborated the importance of MIF in acute pancreatitis. The glucocorticoid- dependent mechanisms seem to play a crucial role in the control of the inflammatory response and tissue damage in L-arginine-induced experimental acute pancreatitis.